Aplikasi Input Dokumen Sensus Pertanian Berbasis Web di Kantor Badan Pusat Statistik Nabire - Ester Ayuk Pusvita; Kevin Yehezkiel Alexander; Arief Rahman Hakim (STMIK Pesat Nabire, 2024)
The central statistics agency is a non-ministerial institution tasked with providing data, one example is agricultural census data. Agricultural census data is data obtained through interviews with farmers conducted directly in the field. The data obtained is so much that sometimes it makes it difficult for employees to manage the data. This data is recorded in a census document, this document will be used for the management process. The author realizes that in doing this task there are many obstacles because in doing data recaps are still done manually or by recording every incoming document, this also makes it difficult for the author to find the required documents. Therefore, solutions are needed in solving the problems faced. The author conducted research so as to find a solution, namely creating a website-based application that is easy to use in inputting census documents and also easy to access for employees in managing data obtained from the field. With the application made, it is expected to help employees in carrying out the process of managing documents.